Pengaruh Maqashid Syariah Index Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Hawari, Rayzul; Puteri, Hesi Eka (Jurnal Ilmiah Global Education, 2024)
The purpose of this study is to analyze the influence of the maqashid sharia index on the value of companies with company size as a moderation variable in the Jakarta Islamic index (JII). This research is classified as quantitative research, the research data collected is secondary data sourced from each annual report/company financial report with a ratio scale. The population in this study is companies that are consistently included in the Jakarta Islamic Index (JII) stock exchange during the 2019-2023 period, while the data analysis technique carried out is differential analysis consisting of pre-research tests, MRA results and hypothesis tests. The data analysis in this study used SPSS software version 29.0.2.0. The results of this study show the influence of . The maqashid sharia index has a positive and significant effect on the value of the company with a significance value of 0.000 < 0.05.The size of the company has a positive effect but is not able to moderate the relationship of the maqashid sharia index to the value of the company with a significance value of 0.180 > 0.05.